Hacia una Taxonomía de Incidentes de Seguridad en Internet - Ortiz Bayona, Zulima; Galindo Pacheco, Francisco (Ingeniería, 2005)
This paper does a tracking for historic evolution of security taxonomy, taking this as fundamental elements in understanding and classification of information about security attacks and incidents,which knowledge of them let us get an optimal handle. It finish suggesting changes on taxonomy based in processes, with events orientation, which is consider the most utile approximation in this topic, especially in Internet.